PEMBERDAYAAN KELOMPOK MASYARAKAT (POKMAS) DALAM PENGELOLAAN SAMPAH DI KELURAHAN CIBADAK - Karmanah, Karmanah; Wibaningwati, Dyah Budibruri; Rusli, Abdul Rahman; Sonani, Nia (Universitas Nusa Bangsa, 2022)
AbstractÂ The problem of household waste in the city of Bogor is included in the Cibadak Village, is still the main problem because the volume continues to increase along with the population are increased. Improper handling of waste will cause environmental pollution and have an impact on peopleâ€™s health. Therefore, it needs to manage waste at the household and community levels through empowering waste management groups at the RW level. The results of community service activities in the Cibadak village already have TPS3R RW 04 and TPS Kukupu RW 08. The manager of TPS3R and TPS Kukuku RW 08 has carried out household waste collection activities as well as sorting organic and non-organic waste. Organic waste has not been processed into compost and non-organic waste has not been used as raw material for handicrafts, but is directly sold to collectors. The household compost produced has the potential to be used as commercial compost because it has compost specifications (based on SNI 19-7030-2004), some of them are black in color and have a total N nutrient content of 0.45%, higher than the minimum limit. Community empowerment can improve the skills of waste managers. Community empowerment in household waste management also has a positive impact because it can improve cleanliness and reduce the level of environmental pollution. In community empowerment activities in household waste management, the partner role is needed for increase the role of TPS3R and TPS managers through community empowerment independently.AbstrakPermasalahan sampah rumah tangga yang ada di Kota Bogor termasuk di Kelurahan Cibadak, masih menjadi masalah utama karena volumenya terus bertambah seiring dengan meningkatnya jumlah penduduk. Penanganan sampah yang kurang baik akan meningkatkan pencemaran lingkungan dan berdampak negatif pada kesehatan masyarakat. Oleh karenanya perlu dilakukan pengelolaan sampah di tingkat rumah tangga dan masyarakat melalui pemberdayaan kelompok-kelompok pengelola sampah di tingkat RW. Hasil kegiatan pengabdian di kelurahan Cibadak sudah ada pada TPS3R RW 04 dan TPS Kukupu RW 08. Pengelola TPS3R dan TPS Kukupu RW 08 sudah melakukan kegiatan pengumpulan sampah rumah tangga serta melakukan pemilahan sampah organik dan non organik. Sampah organik belum diolah menjadi kompos dan sampah non organik belum dimanfaatkan sebagai bahan baku kerajinan, tetapi langsung dijual ke pengepul. Kompos sampah rumah tangga yang dihasilkan berpotensi untuk dijadikan kompos komersial karena memiliki spesifikasi kompos (berdasarkan SNI 19-7030-2004) diantaranya warna kehitaman dan memiliki kandungan hara N total 0,45%, lebih tinggi dari batas minimumnya. Pemberdayaan masyarakat dapat meningkatkan keterampilan mengelola sampah. Pemberdayaan masyarakat dalam pengelolaan sampah rumah tangga juga berdampak positif karena dapat meningkatkan kebersihan dan mengurangi tingkat pencemaran lingkungan. Pada kegiatan pemberdayaan masyarakat dalam pengelolaan sampah rumah tangga, peran mitra sangat diperlukan untuk meningkatkan peran pengelola TPS3R dan TPS melalui pemberdayaan masyarakat secara swadaya.